An Appraisal of Major English Courses for Bachelor’s of Arts - Lamichhane, Sushil (Tribhuvan University Journal, 2017)
The purpose of this article is to identify the strong and weak aspects of the major English courses of three year Bachelor’s programme under the faculty of Humanities and Social Sciences in Tribhuvan University. This article is primarily based on the library research along with the discussions carried out with the teachers of major English. The courses are appropriate and relevant as they impart the knowledge of both literature and literary theories but have holes in the system of teaching learning activities and evaluation system. This article attempts to provide some suggestions for pedagogic implications to the concerned authorities accordingly.